Integrin β1 Increases Stem Cell Survival and Cardiac Function after Myocardial Infarction - Li, Lili; Guan, Qifan; Dai, Shuling; Wei, Wen; Zhang, Yao (Frontiers in Pharmacology, 2017)
Bone mesenchymal stem cells (BMSCs) transplantation is a promising therapeutic approach for myocardial infarction (MI), but its application is limited by poor viability of BMSCs. In this study, we aimed to improve the survival of BMSCs by lentivirus vector mediated overexpression of integrin β1. In vitro study showed that integrin β1 overexpression could facilitate the proliferation of BMSCs under oxygen glucose deprivation condition and regulated the expression of Caspase-3, Bax, Bcl-2, FAK and ILK in BMSCs. Next, MI was induced in rat model and Igtb1BMSCs, NullBMSCs or NatBMSCs were transplanted by intramyocardial injection. One week later, the survival of BMSCs was higher in Itgb1 BMSCs group than in other groups. 4 weeks after transplantation, heart function was significantly improved in Igtb1BMSCs group compared to other groups. The expression levels of Caspase-3 and Bax were decreased while the expression levels of Bcl-2, FAK, ILK and VEGF were increased in the cardiomyocytes of Igtb1BMSCs group compared to other groups. In conclusion, integrin β1 overexpression could increase the survival of BMSCs and improve the efficacy of transplanted BMSCs for MI treatment. The beneficial effects may be mediated by inhibiting the apoptosis of both transplanted BMSCs and cardiomyocytes through adhesion-mediated cell survival signaling.